Use of Mindfulness Sitting Meditation in Chinese American Women in Treatment of Cancer. (March 2017) - Liu, Shan; Qiu, Guang; Louie, Wendy
Background . Very few studies have been conducted to examine the prevalence, frequency, perceived effectiveness, and possible influencing factors of use of meditation in patients with cancer. Objectives . To examine use of mindfulness sitting medication (MSM) in Chinese American women in treatment of cancer, its relationship to specific symptom distress, and possible influencing factors of MSM. Methods . Volunteer participants were recruited through the American Cancer Society support groups. The participants completed a demographic data form, a researcher-developed criteria and checklist for MSM, and the Memorial Symptom Assessment Scale–Short Form. Results . Eighty-nine Chinese American women with a mean age of 58 years completed the questionnaires. Twenty-one patients (24%) reported the use of MSM during active treatment of cancer. Patients who had higher education, better income, better English proficiency, and health insurance were more likely to use MSM. Patients who had more symptom distress also reported to use more MSM. Most patients (20/21) who used meditation considered it effective. After controlling other variables, better English proficiency, breast cancer, and higher symptom distress predicted the use of MSM in Chinese American women in treatment of cancer. Conclusions . About 24% of Chinese American women used MSM in the treatment of cancer and most of them considered it effective. Symptom distress and English proficiency levels predicted the use of MSM. Implications for Practice . Given the effectiveness of MSM, oncology nurses could recommend using MSM in Chinese American women in treatment of cancer, especially for patients who had higher symptom distress.